Recurrent ameloblastoma 30 years after surgical treatment - Miranda, Fábio Vieira de; Iwaki Filho, Liogi; Lima, Valthierre Nunes de; Magro Filho, Osvaldo; Faverani, Leonardo Perez (Journal of Oral Diagnosis, 2017)
Introduction: Ameloblastoma is a locally invasive, slowly growing odontogenic epithelium, which can reach large proportions. It is preferentially located in the region of mandibular molars. The most indicated treatment is resection with safety margin, since its potential for recurrence is high. Objective: To report a case of recurrence the ameloblastoma. Case report: A 60-year-old female patient came to the hospital with difficulty speaking and eating because of the mass inside the mouth and earaches. The extra-buccal physical examination had an increase in volume in the jugal and right temporal regions. At the intra-buccal physical examination there was a nodule approximately 5X6X7 cm, firm at palpation with normal overlying mucosa in color and continuity. The patient reported that 30 years ago she had undergone a surgical procedure to remove an ameloblastoma in the region of the right mandibular body. Imaging revealed a wide extension of the lesion, extending from the symphysis to the cranial base, in the middle cranial fossa region. Previous incisive biopsy revealed the diagnosis of follicular ameloblastoma. Conclusion: Ameloblastoma should be followed for a long period of time because it is a locally infiltrative benign neoplasm that, even when treated with surgery and safety margin, may recur late. The approach taken was the removal of the lesion associated with mandibular reconstruction.